Financial intermediaries and monetary economics - Tobias Adrian; Arturo Estrella (Federal Reserve Bank of New York, 2010)
We reconsider the role of financial intermediaries in monetary economics. We explore the hypothesis that financial intermediaries drive the business cycle by way of their role in determining the price of risk. In this framework, balance sheet quantities emerge as a key indicator of risk appetite and hence of the 'risk-taking channel' of monetary policy. We document evidence that the balance sheets of financial intermediaries reflect the transmission of monetary policy through capital market conditions. We find short-term interest rates to be important in influencing the size of financial intermediary balance sheets. Our findings suggest that the traditional focus on the money stock for the conduct of monetary policy may have more modern counterparts, and we suggest the importance of tracking balance sheet quantities for the conduct of monetary policy.
Keywords: E00; E02; G28; 330; Financial intermediation; monetary policy; risk-taking channel; Finanzintermediär; Lender of Last Resort; Geldpolitik; Transmissionsmechanismus; USA